P144 Evaluation of multidisciplinary pulmonary rehabilitation education delivered by either DVD or spoken talk. (2nd December 2011) - Ward, S; Sewell, L; Singh, S; Singh, S
Abstract : Introduction: Education is a core component of a multidisciplinary Pulmonary Rehabilitation (PR) programme. It is commonly delivered as a spoken session. This can create delivery problems when speakers are unavailable, and adds to the costs of a PR programme. We wanted to evaluate whether videoed presentations would be an acceptable medium for delivering the educational component of an outpatient PR programme. Method: Educational sessions were delivered by the multidisciplinary team at a large teaching hospital, and were professionally filmed. Talks covered were: disease education, healthy eating, medicines, avoidance and exacerbations, exercise and activity, energy conservation, relaxation, managing breathlessness and chest clearance. Patients undertaking PR were asked to evaluate the content and delivery of education sessions using a feedback questionnaire. One patient group evaluated the spoken sessions and a second group evaluated the DVDs. Patients' knowledge was assessed with The Bristol COPD Knowledge Questionnaire (BCKQ) before and after rehabilitation. Results: 117 patients completed feedback forms. A maximum of 69 rated the DVD sessions; mean (SD) age 71.13 (9.69), FEV1 1.25 (0.55) l, COPD 79.7%. A maximum of 48 patients rated the spoken sessions; mean (SD) age 64.94 (12.59), FEV1 1.54 (0.63) l, COPD 69.8%. Not all patients rated all sessions. Delivery was rated as satisfactory or better by 99.16% of patients and 99.49% of patients for DVD and spoken groups, respectively. Initial mean (SD) BCKQ scores were 28.34 (10.30) and 26.41 (13.92) for the DVD and talk group, respectively. Both groups improved BCKQ scores following PR; mean (SD) change 4.53 (10.11) for DVD group and 7.36 (8.98) for talk group, but there were no between group differences (p=0.905). Conclusion: PR patients perceive education delivered by DVD acceptable both in content and medium of delivery. DVDs may be a feasible alternative if multidisciplinary speakers cannot be arranged. This educational medium may also be helpful in reducing the overall costs of rehabilitation, or, if DVDs were to be watched in patients' homes, increasing programme capacity by reducing the duration of each supervised session. For example; for a rolling programme the cost is approximately £1747.60 per programme, per speaker (Agenda for Change Band 6).